1985
DOI: 10.1161/01.hyp.7.5.657
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium in genetic hypertension.

Abstract: HE importance of the calcium ion in muscle contractility and in the optimal functions of the cardiovascular and neurological systems has been recognized since the time of Ringer. A huge body of research data has been generated investigating various facets of the control of blood pressure, including the role of calcium in the biochemistry and physiology of contractile proteins. Interests have been renewed over the past decade on the role of calcium in genetic hypertension at the molecular as well as the organ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
1

Year Published

1986
1986
1993
1993

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 112 publications
0
17
0
1
Order By: Relevance
“…PTH is known to increase intracellular calcium concentration and might thereby directly affect vascular smooth muscle tension. 2 We previously observed that the decrease in diastolic blood pressure to calcium supplementation in offspring with relatively high blood pressure was most clear in subjects with a relatively high plasma PTH or low serum calcium. 32 In one other study, hypertensive subjects with a relatively large urinary calcium excretion showed more pronounced decreases in blood pressure to calcium supplementation compared with those with normal urinary calcium excretion.…”
Section: Discussionmentioning
confidence: 97%
“…PTH is known to increase intracellular calcium concentration and might thereby directly affect vascular smooth muscle tension. 2 We previously observed that the decrease in diastolic blood pressure to calcium supplementation in offspring with relatively high blood pressure was most clear in subjects with a relatively high plasma PTH or low serum calcium. 32 In one other study, hypertensive subjects with a relatively large urinary calcium excretion showed more pronounced decreases in blood pressure to calcium supplementation compared with those with normal urinary calcium excretion.…”
Section: Discussionmentioning
confidence: 97%
“…Young spontaneously hypertensive rats and Dahl salt-sensitive rats have higher 1,25-(OH)2D3 levels than Wistar Kyoto rats and Dahl salt-resistant rats, respectively (16,17). In humans, it has been reported that serum 1,2540H)2D3 is significantly increased in patients with low renin hypertension (18,19).…”
mentioning
confidence: 99%
“…It was also recently reported that 1,25-(OH)2D3 is synthesized in vascular endothelial cells (27) Cell culture. Neonatal rat vascular smooth muscle cells (strain R22D) were obtained from PeterJones (University ofSouthern California) (28) and were used for the present studies at passages [16][17][18][19][20][21][22][23][24][25][26][27][28]. The cells were maintained in Eagle's MEM with 10% FBS, 2% tryptose phosphate broth, penicillin (50 U/ml), and streptomycin (50 U/ml) in a humidified atmosphere of 5% CO2, 95% air at 370C (29).…”
mentioning
confidence: 99%
“…Although the elevated serum 1,25(OH)2D3 concentrations could provide an adequate explanation for the enhanced intestinal Ca transport, additional studies are however necessary to critically evaluate a possible cause-and-effect relationship between these physiologic and chemical alterations. Similarly, although the presence of these changes in the prehypertensive stage of the SHR raises the possibility that they could play a role in the hypertension, more compelling evidence than those summarized (71) depends on future studies specifically evaluating the blood pressure response to correcting these abnormalities in very young SHR.…”
Section: Discussionmentioning
confidence: 99%